Through the Shadows of Roadkill - MacKay, Carley (Humanimalia, 2019)
In this article, I problematize the ways in which we often turn our gaze away from road kill animals. I argue that our relations with road kill warrant ethical kinds of engagement, which I explore through an analysis of death and intimacy. An intimate engagement with animal death strengthens how we understand the complexity of human-road kill relations, while simultaneously providing us with tools for addressing how to engage in these relations in more ethical ways. As I make clear, death does not inhibit our relations with road kill animals, but instead acts as a catalyst for them, enabling us to locate ourselves in the shadows of road kill.